2012
DOI: 10.1177/0265659011428966
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the dynamic in static assessment interaction

Abstract: Traditional approaches to standardized assessment are underpinned by the assumption that between-assessor variation in delivery can effectively be eliminated. However, fine-grained analyses of the administration of such assessments (e.g. Maynard and Marlaire, 1992 ) have established that significant subtle interactional variations occur even in procedures with regimented protocols, and that such variations can demonstrably affect examinee performance. In this article we draw upon the Vygotskian thinking that u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Additionally, Beatriz's movement to the next item in the question sequence ‘perform[s] the dual action of indicating receipt of a response whilst prompting the next [response]’ (Muskett et al . : 92, see also Margutti and Drew 2014). Muskett et al .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, Beatriz's movement to the next item in the question sequence ‘perform[s] the dual action of indicating receipt of a response whilst prompting the next [response]’ (Muskett et al . : 92, see also Margutti and Drew 2014). Muskett et al .…”
Section: Resultsmentioning
confidence: 96%
“…Much research has been devoted to examining this phenomena in classroom contexts (e.g., Mehan , Sinclair and Coulthard , Hellerman , Waring ) assessment contexts (e.g., Marlaire and Maynard , Muskett et al . , Wilkinson ) and to a lesser extent, home contexts (e.g., Kurkul and Corriveau , Tarplee ).…”
Section: Introductionmentioning
confidence: 99%
“…Interactional studies of assessment, while at times highlighting the limitations of these tools, do not aim to undermine them but rather to provide a broader understanding of how they function, for both interactionist researcher and practitioners to build on to. Following the terminology used in Hasson and Botting (2010), Muskett et al (2012) propose that “static” standardized assessments can be complemented by “dynamic” ones that take into account the interactional vicissitudes of the test administration, highlighting competences that the fixed scoring systems would not pick up. As recalled elsewhere (Fasulo, 2015), a rounder evaluation which would engage the child and also gather information from other sources was a default procedure in the early decades of psychological testing, even for the IQ test, so integrating different evaluations is not necessarily disruptive of the ethos of psychological assessments.…”
Section: Assessing Different Childrenmentioning
confidence: 99%
“…However, many have problematized the notion that testing could generally stand as ‘an interactionally ‘neutral’ endeavour that is impervious to examiner influence (or indeed examiner contribution, other than via responses to specific stimuli)’ (Muskett et al . : 88). A large body of psychological work has shown that many aspects can impact the performance measured in diverse testing situations.…”
Section: Introductionmentioning
confidence: 97%
“…CA work has been applied in diverse settings, including doctor–patient consultations (Heath ), standardized assessment situations (Marlaire and Maynard , Maynard , Muskett et al . , involving children with ASD, Wilkinson involving adults with aphasia, and conversations between care staff and clients with intellectual disabilities, Antaki et al . ).…”
Section: Introductionmentioning
confidence: 99%